Knowledge Limits For Realists - العلي, نور; منذر شباني , (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
In this research, we talked about the criticism of the knowledge theory at the realistic approach, the Platonic realism and the problems that can be considered to be related to the realistic existence of the knowledge themes. The first problem we encountered is related to mental essences and how they exist objectively away from the self that carries out the process of knowledge. Then we discussed the nature of wholenesses in Plato in their own existence, and also here we touched on the criticism of these mental wholenesses and the issues associated with the relationship of knowledge to sensory experience. After that, the research moved to deal with the most prominent statements of realism, which are immanence and independence. Then we moved to criticize the concept of common sense in realism, and how this realism was based on the elements and features of this sense. Here we referred to the problems of common sense itself and how they were reflected on the knowledge theory of realism, especially with regard to perception and its themes.